Electronic Word of Mouth Melalui Youtube: Studi Terhadap Beauty Vlogger Kosmetik Wardah - Sonnya Sari; Gati Dwi Yuliana (Fakultas Ilmu Komunikasi Universitas Pancasila, 2017)
This study examines marketing communication by electronic of mouth through a beauty vlogger that is done to communicate the product. The product of this case study is Wardah. This research uses the concept of electronic words of mouth as its analysis blade. This research uses interpretative paradigm with qualitative approach. Informants as research subjects are representative Wardah, beauty vlogger, and audiences. The results show that electronic word of mouth is one form of marketing communication that utilizes the digital media platform as a means of communication. Social media used by beauty vlogger is considered more effective in communicating a product. Wardah uses beauty vlogger as a medium that communicates its marketing through electronic word of mouth in order to reach a broader target with a relatively short time. The effectiveness of an electronic word of mouth dissemination done by beauty vlogger can not be separated from the content of communications submitted in the uploaded video.